Generalized intensity vector and energy density in the spherical harmonic domain: Theory and applications - Herzog, Adrian; Habets, Emanuël (The Journal of the Acoustical Society of America, 2021)
The acoustic intensity vector and energy density are perceptually relevant physical measures of a sound field that can be used in the context of sound field reproduction or acoustic parameter estimation. In this work, weighted spatial averaging of the intensity vector and energy density is investigated, and the results are expressed in terms of the spherical harmonic coefficients of the sound field. Higher-order spherical harmonic coefficients are incorporated by considering radial averaging. This radial averaging is then generalized, yielding the proposed generalized intensity vector and energy density. Direction-of-arrival and diffuseness estimators are constructed based on the generalized intensity vector and energy density. In the evaluation, the proposed parameter estimators are compared to existing state-of-the-art estimators using simulated signals containing directional, diffuse, and sensor-noise components.
CRIS-Team Scopus Importer:2021-07-30